Causal Factors Influencing Entrepreneurial Mindset and Entrepreneurial Intentions among University of Phayao’s Undergraduate Students - Pommi, Chanchai; Kharuhayothin, Tanyatip; Ratanasanguanvongs, Kamolpong; Buntavong, Burin; Khanissarapornpong, Khanis (Journal for Strategy and Enterprise Competitiveness, 2025)
This research aims to examine the influence of entrepreneurial education, entrepreneurial knowledge, and self-efficacy on entrepreneurial mindset and entrepreneurial intentions among undergraduate students at the University of Phayao. The study employed quantitative research methodology, collecting data through an online questionnaire from a stratified random sample of 313 respondents. Data analysis was conducted using partial least squares structural equation modeling (PLS-SEM). The findings revealed that entrepreneurial education had a significant positive influence on both self-efficacy and entrepreneurial mindset, whereas entrepreneurial knowledge significantly positively influenced entrepreneurial mindset but showed no significant effect on self-efficacy. Furthermore, self-efficacy demonstrated a significant positive influence on entrepreneurial mindset, which exhibited a significant positive influence on entrepreneurial intentions. This research provides valuable insights for educational institutions regarding the development of curricula and co-curricular activities that foster entrepreneurial mindset development among students, thereby enhancing the attitudes and skills essential for future entrepreneurial endeavors.